Morphogenetic characterization of West-African populations of Tribolium castaneum Herbst, a pest of stored grains: differentiation in host-breeds and ecotypes - (:unkn) unknown (My University, 2019)
Tribolium castaneum, the primary pest of stored commodities, is a cosmopolitan and polyphagous Coleoptera. Its ability to unroll its development cycle on various food substrates and in all bioclimatic conditions has led to reflections on its morphological and genetic adaptability. The objective of this thesis was to characterize morphologically and genetically the trophic and geographical populations of T. castaneum in the West African zone. Several West African countries have been sampled, of which only seven are home to T. castaneum. Following morphometric, statistical and genotypic studies, the trophic factor is the one that better structures West African individuals. The trophic populations of millet and rice are morphologically and genetically differentiated and each represents a biotype in its own right. There is significant genetic differentiation between West African geographic populations, but this is explained by the different bioclimatic conditions prevailing in these countries. Populations that evolve under the same bioclimatic conditions are not morphogenetically differentiated, with some exceptions (between geographical populations of countries where the Sahelo-Sudanese climate prevails). According to its bioclimatic conditions, three West African ecotypes have been characterized: Sahelian, Sudanese and Sahelo-Sudanese. The bioclimatic factor has a structuring effect on the morphology and genetics of West African populations. The under-structuring of grain marketing in cereal trade sub-space in the West African zone does not have a significant influence on the morphogenetic structuring of these populations because of the geographical position of countries such as Niger and Mali which maintain both cereal trade with several subspaces. Storage conditions in commercial stores favour the morphogenetic intrapopulation diversity of T. castaneum.
Keywords: African Research